Hadith #25 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Waki' bin al-Jarrah وكيع بن الجراح; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘When any one of you enters Al-Khala’ (the toilet), let him not touch his penis with his right hand.'”
Grade:

Hadith #34 - Sunan al-Nasa'i - Abdullah bin Sarjis al-Mazni; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan al-Nasa'i)
“None of you should urinate into a burrow in the ground.” They said to Qatadah: “Why is it disliked to urinate into a burrow in the ground?” He said: “It is said that these are dwelling-places of the jinn.”
Grade:

Hadith #47 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“When any one of you drinks, let him not breathe into the vessel, and when he goes to the toilet let him not touch his penis with his right hand, nor wipe himself with this right hand.”
Grade:

Hadith #198 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Umm Salamah; Yahya bin Ma'in يحيى بن معين; Zaynab bint Abi Salamah (Sunan al-Nasa'i)
“O Messenger of Allah, Allah is not shy to tell the truth. Does a women have to perform Ghusl if she has a wet dream?” He said: “Yes, if she sees water.” Umm Salamah laughed and said: “Do women really have wet dreams?” The Messenger of Allah (ﷺ) said: “How else would her child resemble her?” That is, if she has an emission of the fluid of an orgasm.
Grade:

Hadith #285 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Umm Salamah; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Zaynab bint Abi Salamah (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) and I would sleep under a single blanket when I was menstruating. If anything got on him from me, he would wash that spot and no more, and pray in it, then come back. If anything got on it again from me, he would do likewise and no more, and he would pray in it.”
Grade:

Hadith #338 - Sunan al-Nasa'i - Abu Hurairah; Abu Rafi'; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Khalas bin 'Amr al-Hajri خلاس بن عمرو الهجري; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) commanded that dogs be killed. He said: ‘What do they have to do with dogs?’ And he granted a concession regarding hunting dogs and sheepdogs. And he said: ‘If a dog licks a vessel, wash it seven times, and rub it the eighth time with dust.’ Abu Hurairah differed from him and said: ‘Rub it one time with dust.'”
Grade:

Hadith #367 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني (Sunan al-Nasa'i)
“O Messenger of Allah, I do not become pure, so should I stop praying? He said: “no, that is a vein.” – (One of the narrators) Khalid said, in what I read from him – “and it is not menstruation, so when your period comes, stop praying, and when it goes, wash the blood from yourself and pray.”
Grade:

Hadith #371 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin 'Urwa هشام بن عروة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Zaynab bint Abi Salamah (Sunan al-Nasa'i)
“While I was lying down with the Messenger of Allah (ﷺ) under a blanket, my period came so I slipped away and put on the clothes I used to wear when I was menstruating. The Messenger of Allah (ﷺ) said: ‘Are you menstruating?’ I said: ‘Yes.’ Then he called me to lie down with him under the blanket.” This is the wording of ‘Ubaidullah bin Sa’eed. That is, one of the narrators in one of the chains, as the author reported it through different chains, as he did when it preceded,
Grade:

Hadith #401 - Sunan al-Nasa'i - Ata' bin Abi Rabah عطاء بن أبي رباح; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Jabir ibn 'Abdullah; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“None of you should urinate into standing water which does not flow and then perform Ghusl with it.” (One of the narrators) Sufyan said: “They said to Hisham – meaning Ibn Hassan – ‘Ayyub only attributed this Hadith to Abu Hurairah?’ So he said: ‘If Ayyub is not able to raise up a narration then he does not raise it.'” That is, he narrated it from Abu Hurairah, rather than from him from the Prophet (ﷺ) while others narrated it in Marfu’ form or “raised” to the Prophet
Grade:

Hadith #448 - Sunan al-Nasa'i - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Malik bin Sa'sa'a; Qatada قتادة; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“Busrah bint Safwan told me that.” ‘Urwah sent someone to check that, and she said: “The Messenger of Allah (ﷺ) mentioned what Wudu’ is done for, and said: ‘Touching the penis.'”
Grade:

Hadith #629 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Mas'ud; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Nafi' bin Jubayr bin Mut'im نافع بن جبير بن مطعم; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“The Messenger of Allah (S.A.W) commanded Bilal to say the phrases of the Adhan twice and the phrases of the Iqamah once.”
Grade:

Hadith #638 - Sunan al-Nasa'i - Abdullah bin Mahayraz عبد الله بن محيريز; Abu Mahdhura al-Jumhi; Amir bin Abd al-Wahd عامر بن عبد الواحد الأحول البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Makhul al-Shami/al-Damashiqi مكحول الشامي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله (Sunan al-Nasa'i)
“Abu Qilabah said to me (Ayyub): He (‘Amr) is still alive, do you want to meet him?” I met him and asked him, and he said: “When Makkah was conquered, all the people hastened to announce their Islam. My father went to announce the Islam of the poeple of our village, and when he came back we went to see him and he said: ‘By Allah, I have indeed come to you from the Messenger of Allah (S.A.W)’. He said: ‘Pray such and such a prayer at such and such a time, pray such and such a prayer
Grade:

Hadith #653 - Sunan al-Nasa'i - al-Bara' bin Azib bin al-Harith; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan al-Nasa'i)
(Another chain) from Ibrahim, from Al-Aswad, with similar narration.
Grade:

Hadith #890 - Sunan al-Nasa'i - Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ibn Sirin محمد بن سيرين الأنصاري; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
X”I heard Abu Uthman narrate that Ibn Mas’ud said: ‘The Prophet (ﷺ) saw me when I had placed my left hand on my right in prayer. He took hold of my right hand and placed it on my left.'”
Grade:

Hadith #976 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
His father said: “The Messenger of Allah (ﷺ) used to lead us in prayer, and he would recite in the first two rak’ahs and make us hear some verses. And he would make the (first) Rak’ah lengthy in Zuhr, and also the first rak’ah.” Meaning in Subh.
Grade:

Hadith #1077 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I shall explain to you the prayer of the Messenger of Allah (ﷺ).” He said: “Abu Hurairah used to say the Qunut in the last rak’ah of the Zuhr prayer, and the later Isha’ prayer, and the Subh, after saying ‘Sami Allahu liman hamidah.’ He would pray for the believers and curse the disbelievers.'”
Grade:

Hadith #1079 - Sunan al-Nasa'i - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said the Qunut for a month.”- (One of the narrators) Shu’bah said: “He cursed some men.” Hisham said: “He supplicated against some of the tribes of Arabs.”-“Then he stopped doing that after bowing.” This is what Hisham said. Shu’bah said, narrating from Qatadah, from Anas that the Prophet (ﷺ) said the Qunut for a month, cursing Ri’l, Dhawkan and Lihyan.
Grade:

Hadith #1087 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Malik bin al-Hwyrth; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Nsr bin 'Asim al-Lythy نصر بن عاصم الليثي البصري; Qatada قتادة (Sunan al-Nasa'i)
He saw the Prophet (ﷺ) raise his hands when praying, when he bowed, when he raised his head from bowing, when he prostrated and when he raised his head from prostrating, until they were in level with the top part of his ears.
Grade:

Hadith #1143 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Malik bin al-Hwyrth; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Nsr bin 'Asim al-Lythy نصر بن عاصم الليثي البصري; Qatada قتادة (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) came out to us for one of the nighttime prayers, and he was carrying Hasan or Husain. The Messenger of Allah (ﷺ) came forward and put him down, then he said the Takbir and started to pray. He prostrated during his prayer, and made the prostration lengthy.” My father said: “I raised my head and saw the child on the back of the Messenger of Allah (ﷺ) while he was prostrating so I went back to my prostration. When the Messenger of Allah (ﷺ) finished praying
Grade:

Hadith #1169 - Sunan al-Nasa'i - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Mas'ud; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي (Sunan al-Nasa'i)
“We used not to know what to say when we prayed, then the Messenger of Allah (ﷺ) taught us some eloquent and concise words. He said to us: ‘Say: “At-tahiyyatu lillahi was-salawatu wat-tayyibat, as-salamu ‘alaika ayyuhan-Nabiyyu wa rahmatAllahi wa baraktuhu. As-salamu ‘alaina wa ‘ala ‘ibad illahis-salihin, ashahdu an la illaha ill-Allah wa ashhadu anna Muhammadan ‘abduhu wa rasuluhu (Allah compliments, prayers and pure words are due to Allah. Peace be upon you, O Prophet, and th
Grade:

Hadith #1253 - Sunan al-Nasa'i - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Bashr bin Hilal al-Swaf بشر بن هلال الصواف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
The Messenger of Allah (ﷺ) said: “Whoever has doubt during his prayer, let him prostrate twice.” (One of the narrators) Hajjaj said: “After he has said the taslim.” (Another of them) Rawh said: “While he is sitting.”
Grade:

Hadith #1366 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Jabir ibn 'Abdullah; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Umar ibn al-Khattab; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“We fasted Ramadan with the Messenger of Allah (ﷺ), and the Prophet (ﷺ) did not lead us in Qiyam until there were seven days left of the month, then he led us in Qiyam until one-third of the night had passed. Then, when there were six days left, he did not lead us in Qiyam. When there were five days left, he led us in praying Qiyam until half the night had passed. We said: ‘O Messenger of Allah (SA), why don’t you lead us in praying Qiyam for the rest of the night?’ He said: ‘If a
Grade:

Hadith #1471 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Ata' bin Abi Rabah عطاء بن أبي رباح; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Ubaid bin 'Umayr bin Qatada عبيد بن عمير بن قتادة (Sunan al-Nasa'i)
“The sun was eclipsed during the life of the Prophet (ﷺ). The Messenger of Allah (ﷺ) went out to the masjid and stood and said the takbir, and the people formed rows behind him. He bowed four times and prostrated four times, and the eclipse ended before he finished.”
Grade:

Hadith #1487 - Sunan al-Nasa'i - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan al-Nasa'i)
“The sun eclipsed during the time of the Messenger of Allah (ﷺ). The Messenger of Allah (ﷺ) got up to pray, and those who were with him also got up. He stood for a long time, then he bowed for a long time, then he raised his head and (then) prostrated for a long time. Then he raised his head and sat for a long time. Then he prostrated for a long time, then he raised his head and stood up, and he did in the second rak’ah the same as he had done in the first, standing, bowing, prostrating
Grade:

Hadith #1488 - Sunan al-Nasa'i - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; al-Nu'man bin Bashir ibn Sa'd; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan al-Nasa'i)
“The sun eclipsed during the time of the Messenger of Allah (ﷺ). He stood and led the people in prayer. He stood for a long time, then he bowed for a long time, then he stood for a long time that was shorter than the first time, then he bowed for a long time that was shorter than the first time. Then he prostrated for a long time, then he sat up, then he prostrated for a long time that was shorter than the first time. Then he stood up and bowed twice again, doing the same again. Then he pros
Grade:

Hadith #1490 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; al-Nu'man bin Bashir ibn Sa'd; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Sunan al-Nasa'i)
“The sun eclipsed during the time of the Messenger of Allah (ﷺ) and he rushed out, dragging his cloak until he came to the masjid. He continued leading us in prayer until the eclipse ended. When it ended, he said: ‘People claim that the eclipse of the sun and moon only happen when a great man dies, but that is not so. Eclipses of the sun and the moon do not happen for the death or birth of anyone, but they are signs from Allah (SWT), the Mighty and Sublime. When Allah, the Mighty and Subli
Grade:

Hadith #1642 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Ma'in يحيى بن معين (Sunan al-Nasa'i)
The Prophet (ﷺ) said: ‘On the night on which I was taken on the Night Journey, I passed by Musa and he was praying in his grave.’
Grade:

Hadith #1651 - Sunan al-Nasa'i - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; al-Hasan al-Basri الحسن البصري; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Sa'd bin Hisham bin 'Amir سعد بن هشام بن عامر (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) used to pray for a long time at night. If he started to pray standing, he would bow standing and if he started to pray sitting, he would bow sitting.”
Grade:

Hadith #1719 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Sa'd bin Hisham bin 'Amir سعد بن هشام بن عامر; Zararah bin Awfa al-'Amiri al-Harshi زرارة بن أوفى العامري الحرشي (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) used to pray witr with five and seven rak’ahs which he did not separate with any taslim nor talk.”
Grade:

Hadith #1755 - Sunan al-Nasa'i - Azrh bin 'Abdur Rahman عزرة بن عبد الرحمن بن زرارة الخزاعي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Qatada قتادة; Sa'id bin 'Abdur Rahman bin Abza سعيد بن عبد الرحمن بن أبزي (Sunan al-Nasa'i)
The Messenger of Allah (ﷺ) used to recite in witr: “Glorify the Name of Your Lord, the Most High;’ and “Say: O you disbelievers!’; and ‘Say: He is Allah, (the) One.” And after he had said the salam, he would say: Subhanal-Malikil-Quddus (Glory be to the Sovereign, the Most Holy) raising his voice the third time.”
Grade:

Hadith #1769 - Sunan al-Nasa'i - Hafsa bint Umar; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Umar; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Nafie' نافع مولى ابن عمر; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said to me: ‘O Abdullah do not be like so-and-so; he used to pray Qiyam Al-Lail and then he stopped.'”
Grade:

Hadith #1781 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“When dawn came, the Messenger of Allah (ﷺ) would not pray anything but two brief rak’ahs.”
Grade:

Hadith #1833 - Sunan al-Nasa'i - Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Qsamh bin Zuhyr al-Mazny قسامة بن زهير المازني (Sunan al-Nasa'i)
“The believer dies with sweat on his forehead.”
Grade:

Hadith #1917 - Sunan al-Nasa'i - Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Hisham bin 'Urwa هشام بن عروة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“My father told me: I witnessed the funeral of ‘Abdur-Rahamn bin Samurah. Ziyad came out, walking in front of the bier, and some men from the family of ‘Abdur-Rahman and their freed slaves came out, facing the bier and walking backward, saying: ‘Slow down, slow down, may Allah bless you.’ And they were walking slowly. Then when they were partway to Al-Mrbad, Abu Bakrah joined us on his mule. When he saw what they were doing, he rushed to them on his mule, brandishing his whip, and said
Grade:

Hadith #1922 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Hisham bin 'Urwa هشام بن عروة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Ubaidullah bin Mqsm عبيد الله بن مقسم; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘When you see a funeral, stand up, and whoever follows it, let him not sit down until (the body) is placed (in the grave).”
Grade:

Hadith #1957 - Sunan al-Nasa'i - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Imran bin Husain; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah was asked about he children of the idolators and he said: ‘Allah knows best what they would have done.”‘
Grade:

Hadith #2155 - Sunan al-Nasa'i - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Qatada قتادة; Waki' bin al-Jarrah وكيع بن الجراح; Zayd ibn Thabit (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Eat Sahur, for in Sahur there is blessing.”
Grade:

Hadith #2156 - Sunan al-Nasa'i - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Qatada قتادة; Zayd ibn Thabit (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Eat Sahur, for in Sahur there is blessing.” (Hasan) Abu ‘Abdur-Rahman (An-Nasai) said: In this narration of Yahya bin Saeed, its chain is Hasan but it is Munkar, and I fear that the error is from Muhammad bin Fudail.
Grade:

Hadith #2180 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“U never saw the Messenger of Allah fast two consecutive months, but he used to join shaban to Ramadan.” ‘
Grade:

Hadith #2183 - Sunan al-Nasa'i - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Aisha bint Abi Bakr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ibn Sirin محمد بن سيرين الأنصاري; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan al-Nasa'i)
“One of us (women) would miss some fasts in Ramadan and she would not be able to make it up until Shaban began, and the Messenger of Allah did not fast in any month as he fasted in Shaban; he used to fast all of it, except a little, he used to fast all of it.” ‘
Grade:

Hadith #2294 - Sunan al-Nasa'i - Azhar bin al-Qasim al-Rasby أزهر بن القاسم الراسبي; Hamza bin 'Amr al-Aslami; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Rafa'i محمد بن رافع; Qatada قتادة; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث (Sunan al-Nasa'i)
the Messenger of Allah fasted while traveling until he reached Qudaid, then he called for a cup of milk and drank and broke his fast; he and his Companions.
Grade:

Hadith #2305 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Hamza bin 'Amr al-Aslami; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Urwa ibn al-Zubayr عروة بن الزبير (Sunan al-Nasa'i)
“I used to fast continually at the time of the Messenger of Allah. I said: ‘O continually while traveling.’ He said: ‘If you wish then fast, and if you wish then do not fast.”‘
Grade:

Hadith #2509 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Ibn Sirin محمد بن سيرين الأنصاري; Mkhld bin Yazid al-Quraishi مخلد بن يزيد القرشي الحراني (Sunan al-Nasa'i)
“The Messenger of Allah enjoined Zakatul-Fitr, a Sa’ of dates or a Sa of barley, upon the free person and the slave, male and female, young and old, among the Muslims. He commanded that it be given before the people went out to the (‘fd) prayer.”
Grade:

Hadith #2581 - Sunan al-Nasa'i - Abu Sa'id al-Khudri; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Hilal bin Abi Maymuna هلال بن علي بن أسامة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Sunan al-Nasa'i)
“There are four whom Allah, the Mighty and Sublime, hates: The vendor who sells his wares by means of false oaths, the poor man who shows off, the old man who commits Zina and the Imam who is unjust.”
Grade:

Hadith #2643 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Fadl ibn al-'Abbas; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Yahya bin Abi Ishaq يحيى بن أبي إسحاق; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“A man from Khath’am came to the Messenger of Allah and said: ‘My father is an old man who cannot ride, and the command of Allah to perform Hajj has come. Will it be good enough if I perform Hajj on his behalf?’ He said: ‘Are you the oldest of his children?’ He said: ‘Yes.’ He said: ‘Don’t you think that if he owed a debt you would pay it off?, He’ said: ‘Yes.’ He said: ‘then perform Hajj on his behalf.”'(Daif)
Grade:

Hadith #2791 - Sunan al-Nasa'i - Abu Hsan al-A'rj أبو حسان الأعرج; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Qatada قتادة; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan al-Nasa'i)
That the Messenger of Allah used to send sheep as a Hadi,
Grade:

Hadith #2824 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
he gave the Messenger of Allah an onager when he was in Al-Abwa or in Waddan, but the Messenger of Allah gave it back to him. “And when the Messenger of Allah saw the expression on my face he said: “We only gave it back to you because we are in Ihram.'”
Grade:

Hadith #2831 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ibrahim bin Muhammad bin 'Ar'ara إبراهيم بن محمد بن عرعرة; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Ishaq al-Saghani محمد بن إسحاق الصغاني; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“Abdullah bin Abu Qatadah said that his father told him, that he went out with the Messenger of Allah on the campaign of Al-Hudaybiyah. He said: ‘They entered Ihram for ‘Umrah apart from me. I hunted an onager and fed my companions with it, when they were in Ihram. Then, I went to the Messenger of Allah and told him that we had some of it meat left over. HE said: Eat, and they were in Ihram.'”.
Grade:

Hadith #3012 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Sunan al-Nasa'i)
“I was with Ibn Abbas in Arafat and he said: ‘Why do I not hear the people reciting Talbiyah?’ I said: They are afraid of Muawiyah.’ So Ibn Abbas went out of his tent and said: “Labbaik Allahumma Labbaik, Labbaik! They are only forsaking the Sunnah out of hatred for Ali.'”
Grade:

Hadith #3143 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Ma'dan bin Abi Talha معدان بن أبي طلحة ويقال بن طلحة; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Salm bin Abi al-Ja'd سالم بن أبي الجعد (Sunan al-Nasa'i)
“O Shaikh, tell me of a Hadith that you heard from the Messenger of Allah (ﷺ).” (He said: “Yes; I heard the Messenger of Allah (ﷺ)) say: ‘The first of people for whom judgment will be passed on the Day of Resurrection are three. A man who was martyred. He will be brought and Allah will remind him of His blessings and he will acknowledge them. He will say: What did you do with them? He will say: I fought for Your sake until I was martyred. He will say: You are lying. You fought so tha
Grade:

Hadith #3214 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Samra bin Jundub (Sunan al-Nasa'i)
It was narrated from ‘Alqamah and Al-Aswad that ‘Abdullah said: “The Messenger of Allah said to us: ‘Whoever among you can afford it, let him get married, and whoever cannot then he should fast, for it will be a restraint (wija’) for him.'” Abu Abdur-Rahman said: (The mention of) Al-Aswad in this hadith is not preserved.
Grade:

Hadith #3242 - Sunan al-Nasa'i - Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan al-Nasa'i)
It was narrated from ‘Urwah, that ‘Aishah said: “The Messenger of Allah married me in Shawwal and my marriage was consummated in Shawwal.” –‘Aishah liked for her women’s marriages to be consummated in Shawwal –“and which of his wives was more beloved to him than me?”
Grade:

Hadith #3267 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“A previously married woman has more right to decide about herself (with regard to marriage) than her guardian, and an orphan girl should be consulted, and her permission is her silence.”
Grade:

Hadith #3309 - Sunan al-Nasa'i - Abdullah ibn al-Zubayr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Ma'in يحيى بن معين (Sunan al-Nasa'i)
“I heard ‘Aishah say: The Messenger of Allah said: ‘What becomes unlawful (for marriage) through breast-feeding is that which becomes unlawful through birth.'”
Grade:

Hadith #3448 - Sunan al-Nasa'i - Abdur Rahman bin al-Qasim عبد الرحمن بن القاسم بن محمد بن أبي بكر; Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Sunan al-Nasa'i)
“The Messenger of Allah gave his wives the choice but that was not a divorce.”
Grade:

Hadith #3474 - Sunan al-Nasa'i - Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Azrh bin 'Abdur Rahman عزرة بن عبد الرحمن بن زرارة الخزاعي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
“I asked Anas bin Malik about that, as I thought that he had knowledge of that. He said: ‘Hilal bin Umayyah accused his wife (of committing adultery) with Sharik bin As-Sahma’, who was the brother of Al-Bara’ bin Malik through his mother. He was the first one who engaged in the procedure of Li’an. The Messenger of Allah conducted the procedure of Li’an between them, then he said: “Look and see, if she produces a child who is white, with straight hair and Qadiy’a eyes, then he bel
Grade:

Hadith #3534 - Sunan al-Nasa'i - Abu Ahmed al-Mu'dab الحسين بن محمد بن بهرام - أبو علي المؤدب; Hafsa bint Sirin حفصة بنت سيرين; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Umm Atiyyah Ansariyah (Sunan al-Nasa'i)
“She was in a remote house. She came with her brothers to the Messenger of Allah and told him (about the situation) and he granted her a concession. When she was leaving he called her back and said: ‘Stay in your house until the term prescribed is fulfilled.'”
Grade:

Hadith #3664 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Qatada قتادة; Sa'd ibn 'Ubadah; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan al-Nasa'i)
“My mother has died and she had a vow to fulfill. Will it suffice if I free a slave on her behalf?” He said: “Free a slave on behalf of your mother.”
Grade:

Hadith #3665 - Sunan al-Nasa'i - al-Husain bin Hryth الحسين بن حريث; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Qatada قتادة; Sa'd ibn 'Ubadah; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan al-Nasa'i)
“Fulfill it on her behalf.”
Grade:

Hadith #3676 - Sunan al-Nasa'i - Ahmed bin Harb bin Muhammad أحمد بن حرب بن محمد; al-Nu'man bin Bashir ibn Sa'd; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Sunan al-Nasa'i)
“I am poor and I do not have anything, and I have an orphan (under my care).” He said: “Eat from the property of your orphan without being extravagant, wasteful or keeping it as capital for yourself.”
Grade:

Hadith #3724 - Sunan al-Nasa'i - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Tawus bin Kaysan طاوس; Zayd bin Akhzm زيد بن أخزم (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Umra (a gift given for life) is for the heir.'”
Grade:

Hadith #3737 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“The Messenger of Allah forbade ‘Umra and Ruqba.” I said: “What is Ruqba?” He said: “When one man says to another: ‘This belongs to you for the rest of your life.’ But if you do that, it is permissible.”
Grade:

Hadith #3750 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Umra (a lifelong gift) belongs to the one to whom it was given; it belongs to him and to his heirs, and is inherited by those among his descendants who inherit from him.'”
Grade:

Hadith #3755 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ibn Sirin محمد بن سيرين الأنصاري; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan al-Nasa'i)
“Abu Salamah bin ‘Abdur-Rahman narrated to me, that Jabir told him: ‘The Messenger of Allah ruled that whoever gives a lifelong gift to a man, it belongs to him and to his heirs. It belongs to the one to whom it was given, on the basis of ‘Umra. It will be inherited from its recipient according to Allah’s (injunctions on) inheritance and its rights.'”
Grade:

Hadith #3774 - Sunan al-Nasa'i - Abdur Rahman bin Samra; Ahmed bin Suliaman أحمد بن سليمان; al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“A man from Banu Ghifar told me, in the gathering of Salim bin ‘Abdullah, Salim bin ‘Abdullah said: ‘I heard ‘Abdullah -that is, Ibn ‘Umar- say: “The Messenger of Allah said: ‘Allah forbids you to swear by your forefathers.'”‘”
Grade:

Hadith #3916 - Sunan al-Nasa'i - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Rafi' bin Khadij bin Rafi' (Sunan al-Nasa'i)
“The Messenger of Allah forbade leasing land.” Ibn Shihab said: “Rafi was asked after that: ‘How did they lease land?’ He said: ‘In return for a set amount of food (produce), and it was stipulated that we would have whatever grew on the banks of the streams and springs.'”
Grade:

Hadith #4047 - Sunan al-Nasa'i - Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan al-Nasa'i)
“Some people raided the milk camels of the Messenger of Allah . He caught them and had their hands and feet cut off and their eyes gouged out.”
Grade:

Hadith #4064 - Sunan al-Nasa'i - Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Qatada قتادة (Sunan al-Nasa'i)
“Any slave who runs away to the land of Shirk, it becomes permissible to shed his blood.”
Grade:

Hadith #4065 - Sunan al-Nasa'i - Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan al-Nasa'i)
“Any slave who runs away to the land of Shirk, it becomes permissible to shed his blood.”
Grade:

Hadith #4243 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jwn bin Qtad'h bin al-A'wr جون بن قتادة بن الأعور; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Salmah bin al-Mahbaq (Sunan al-Nasa'i)
“I said: ‘O Messenger of Allah, we used to offer sacrifices during the Jahiliyyah in Rajab, and eat of (their meat) and offer some to those who came to us.’ The Messenger of Allah said: ‘There is nothing wrong with that.”‘ (One of the narrators) Waki bin ‘Udus said: “I will not leave it.”
Grade:

Hadith #4354 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“While we were traveling with the Prophet in part of Athaya Ar-Rawha and they were in Ihram, we saw a wounded onager, the Messenger of Allah said: “Leave it, for soon the one who wounded it will come,’ then a man from Bahz came, and he was the one who had wounded the onager. He said: ‘O Messenger of Allah, it is up to you what you do with this onager,’ The Messenger of Allah ordered Abu Bakr to distribute it among the people.”
Grade:

Hadith #4360 - Sunan al-Nasa'i - Abu Hurairah; al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan al-Nasa'i)
“Its water is pure (and Purification) and its ‘dead meat’ is permissible (to eat).”
Grade:

Hadith #4381 - Sunan al-Nasa'i - B'jh bin 'Abdullah بعجة بن عبد الله بن بدر; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Uqba bin 'Amir al-Juhayni; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“I heard the Messenger of Allah say” – and he gestured with his fingers, but his fingers were shorter than the fingers of the Messenger of Allah – he said “It is not permissible to offer as a sacrifice an animal that clearly has one bad eye, a lame animal that is obviously lame, as sick animal that is obviously sick, or an animals that is so emaciated that it is as if there is no marrow in its bones.”
Grade:

Hadith #4448 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Ikrama عكرمة; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Qatada قتادة (Sunan al-Nasa'i)
“The Messenger of Allah said: An animal that has been taken as a target is not lawful.”
Grade:

Hadith #4481 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Samra bin Jundub (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘The two parties to a transaction both have the choice so long as they have not separated or they have chosen to conclude the transaction.’ Or perhaps Nafi said: “Or one of them has said to the other: ‘Decide! (Sahih )
Grade:

Hadith #4525 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“The Messenger of Allah forbade two kinds of garments and two kinds of transactions. As for the two kinds of transactions, they are Mulamash and Munabadhaha. Munabadha is when a man says, ‘I throw this garment, and the transaction becomes binding, and Mulamasah is when a man touches it with his had, without spreading it out and checking it, and once he touches it, the transaction becomes binding.”
Grade:

Hadith #4555 - Sunan al-Nasa'i - Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah was asked about (buying) fresh dates with dried dates, and he said to those who were around him: ‘Will fresh dates decrease (in weight or volume) when they dry out?” they said Yes,’ so he forbade that.”
Grade:

Hadith #4610 - Sunan al-Nasa'i - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Qatada قتادة (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever buys food let him not sell it until he takes possession of it. Ibn ‘Abbas said: “I think the same applies to everything else as to food.”
Grade:

Hadith #4651 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Ikrama عكرمة; Sufyan bin Habib al-Basri سفيان بن حبيب البصري; Yusuf bin Hmad يوسف بن حماد (Sunan al-Nasa'i)
“We were traveling with the Messenger of Allah and I was riding a camel. The Messenger of Allah said to me: ‘Will you sell it to me for such and such, may Allah forgive you?’, I said, I said, ‘Yes, it is yours, O Prophet of Allah.’ He said: ‘Will you sell it to me for such and such, may Allah forgive your?’ I said: ‘Yes, it is yours, O Prophet of “Allah.’ He said: ‘Will you sell it to me for such and such, may Allah forgives you?’ I said: ‘Yes, it is yours. ”'(One of
Grade:

Hadith #4736 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Qatada قتادة; Samra bin Jundub; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي (Sunan al-Nasa'i)
“I was sitting with the Messenger of Allah when a man came with a string around his neck and said: ‘O Messenger of Allah, this man and my brother were digging a hole, and he raised his pickax and struck his companion in the head, Killing him. ‘The Prophet said: ‘Forgive him,’ but he refused and said: ‘O Prophet of Allah, this man and my brother were digging a whole, and he raised his pickax and struck his companion in the head, killing him.’ The Prophet said: ‘Forgive him,’ but
Grade:

Hadith #4751 - Sunan al-Nasa'i - al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Imran bin Husain; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan al-Nasa'i)
a Jew took some jewelry from a girl, then he crushed her head between two rocks. They found her as she was breathing her last, and they took her around among the people (saying); “Was it this one? Was it this one?” (When) she said yes, the Messenger of Allah ordered that his head be crushed between two rocks.
Grade:

Hadith #4754 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Samra bin Jundub (Sunan al-Nasa'i)
“I heard Abu Juhaifah say: ‘We asked ‘Ali: “Do you have anything from the Messenger of Allah apart from the Qur’an?” He said: “No, by the One who splits the seeds and creates the soul, unless Allah gives a slave understanding of His Book, or except this sheet.” I said: “What is in the sheet?” He said: “In it are (the regulations concerning) blood money and the freeing of captives and (the rule) that no Muslim should be killed for killing a disbeliever.”
Grade:

Hadith #4771 - Sunan al-Nasa'i - Ata' bin Abi Rabah عطاء بن أبي رباح; Badayl bin Maysarah بديل بن ميسرة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Safwan bin Y'ala bin Umayya صفوان بن يعلى بن أمية (Sunan al-Nasa'i)
Ya’la said, concerning the one who bit (another), and his front tooth fell out, that the Prophet said: “There is no Diyah for you.” (Sahih )
Grade:

Hadith #4860 - Sunan al-Nasa'i - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan al-Nasa'i)
“When the Messenger of Allah conquered Makkah, he said in his Khutbah: “(The Diyah) for fingers is ten each.”
Grade:

Hadith #4892 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“Safwina was slleping in the Masjid with his Rida’ beneath him, and it was stolen. He got up, and the man had gone, but he caught up with him, and took him to the prophet, who ordered that his hand be cut off. Safwan said; ‘O Messenger of Allah, my Rida ‘is not worth cutting off a man’s hand for. ‘He said ‘Why did you not say that before you brought him to me
Grade:

Hadith #4911 - Sunan al-Nasa'i - Abdullah bin al-Sabah bin 'Abdullah عبد الله بن الصباح بن عبد الله; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Qatada قتادة (Sunan al-Nasa'i)
“Who will speak concerning her?” They said: “Who would dare to do that except Usamah bin Zaid, the beloved of the Messenger of Allah?” said: “Those who came before you were destroyed because whenever a noble person among them stole they would let him go. But if a person who was weak stole, they would carry out the Hadd punishment. By Allah, if Fatimah, the daughter of Muhammad, were to steal, I would ct off her hand.”
Grade:

Hadith #5027 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
‘Ali said: “The Unlettered Prophet made a covenant with me, that none but a believer would love me, and none but a hypocrite would hate me.”
Grade:

Hadith #5092 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Mu'awiya ibn Abu Sufyan; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“My father and I came to the Prophet and he had dyed his beard with Henna.”
Grade:

Hadith #5139 - Sunan al-Nasa'i - Asma' bint Yazid bin al-Sakan; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
The Messenger of Allah said: “If one of you wants to attend ‘Isha’ prayer, let her not touch perfume.”
Grade:

Hadith #5140 - Sunan al-Nasa'i - Amr bin Marthad, Abu Asma' al-Rahbi عمرو بن مرثد أبو أسماء الرحبي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Zayd ibn Harithah (Sunan al-Nasa'i)
The Prophet of Allah said: “If any one of you goes out to the Masjid, let her not go near perfume.”
Grade:

Hadith #5184 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Ubaida bin 'Amr al-Salamani عبيدة بن عمرو; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“I heard ‘Ali say: ‘The Messenger of Allah forbade me- but I do not say that he forbade you- from wearing gold rings, Al-Qassi, and garments dyed with safflower, and reciting Qur’an while bowing.'”
Grade:

Hadith #5315 - Sunan al-Nasa'i - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan al-Nasa'i)
He asked ‘Abdullah bin ‘Abbas about wearing silk. He said: “Ask ‘Aishah.” “So I asked ‘Aishah and she said: ‘Ask ‘Abdullah bin ‘Umar.’ So I asked Ibn ‘Umar and he said: ‘Abu Hafs told me, that the Messenger of Allah said: “Whoever wears silk in this world will have no share in the Hereafter.”
Grade:

Hadith #5316 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Jubayr bin Nufayr al-Hadrami; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Khalid bin Ma'dan خالد بن معدان; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
That the Messenger of Allah said: “Silk is only worn by one who has no share.”
Grade:

Hadith #5330 - Sunan al-Nasa'i - Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“A woman brought a Burdah” – Sahl said: “Do you know what a Burdah is?” They said: “Yes, it is a cloak with two woven borders” – and she said: ‘O Messenger of Allah, I wove this with my own hands for you to wear.’ The Messenger of Allah took it as he had need of it, then he came out to us and he was wearing it as his Izar (lower garment).”
Grade:

Hadith #5351 - Sunan al-Nasa'i - Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mas'ud bin Jwyryh bin Da'ud مسعود بن جويرية بن داود; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ishtimal As-Samma’ and wrapping oneself in a single garment (that did not cover the private parts).”
Grade:

Hadith #5368 - Sunan al-Nasa'i - Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Amr bin Aws bin Abi Aws عمرو بن أوس بن أبي أوس; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Safwan bin 'Isa al-Zhry صفوان بن عيسى الزهري أبو محمد البصري (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever makes an image will be punished until (he is commanded) to breathe a soul into it, and he will not be able to do so.'”
Grade:

Hadith #5375 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Qatada قتادة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi al-Hasan سعيد بن أبي الحسن; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“The Messenger of Allah would not pray in our blankets.”
Grade:

Hadith #5394 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Fadl ibn al-'Abbas; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Yahya bin Abi Ishaq يحيى بن أبي إسحاق; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
The Prophet said: “You will be keen for governorship but it will be regret and loss on the Day of Resurrection. What a good position it is when they are alive, but how miserable their state when they die (and leave it behind).”
Grade:

Hadith #5448 - Sunan al-Nasa'i - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan al-Nasa'i)
“I came to the Messenger of Allah while he was riding, and I put my hand on his foot and said: ‘Teach me Surah Hud, teach me Surah Yusuf. He said: ‘You will never recite anything more precious before Allah, the Mighty and Sublime, than: ‘Say: I seek refuge with (Allah) the Lord of the daybreak.'”
Grade:

Hadith #5459 - Sunan al-Nasa'i - Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan al-Nasa'i)
“The Messenger of Allah had supplications that he never neglected. He used to say: ‘Allahumma inni a’udhu bika minal-hammi, wal-hazani, wal-‘ajzi, wal-kasali, wal-bukhli, wal-jubni, wad-daini, wa ghalabatar-rijal (O Allah, I seek refuge with You from worry, grief, incapacity, laziness, miserliness, cowardice, debt, and being overpowered by (other) men.)”
Grade:

Hadith #5566 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ad-Dubba’, Al-Hantam, Al-Muzaffat, and An-Naqir, and that Al-Busr be mixed with dried dates, and that raisins be mixed with dried dates, and he wrote to the people of Hajar saying: ‘Do not mix raisins and dried dates together.'”
Grade:

Hadith #5646 - Sunan al-Nasa'i - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس (Sunan al-Nasa'i)
“I heard the Messenger of Allah forbidding drinks made in Dubba’ (gourds), Hantam or Muzaffat, that were not oil or vinegar.”
Grade:

Hadith #2150 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي (Sunan Abi Dawud)
Ibn Masu’d reported the Apostle of Allaah(ﷺ) as saying “ A woman should not rub her body directly with the body of another woman so that she describes it to her husband as if he were looking at her.”
Grade: Sahih

Hadith #2189 - Sunan Abi Dawud - Abdul 'Aziz bin 'Abdul Samad عبد العزيز بن عبد الصمد; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Matr bin Tahman al-Waraq مطر بن طهمان الوراق أبو رجاء الخراساني; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
The Prophet (ﷺ) said: The divorce of a slave-woman consists in saying it twice and her waiting period is two menstrual courses (qur’) AbuAsim said: A similar tradition has been narrated to me by Muzahir and al-Qasim on the authority of Aisha from the Prophet (ﷺ), except that he said: And her waiting period (‘iddah) is two courses. Abu Dawud said: This tradition is obscure.
Grade: Da'if

Hadith #2204 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
I asked Ayyub: Do you know anyone who narrates the tradition narrated by Al-Hasan about uttering the words (addressing wife). “Your matter is in your hand”? He replied: No, except something similar transmitted by Qatadah from Kathir, the client of Samurah, from AbuSalamah on the authority of AbuHurayrah from the Prophet (ﷺ). Ayyub said: Kathir then came to us; so I asked him (about this matter). He replied: I never narrated it. I mentioned it to Qatadah who said: Yes (he narrated it) but h
Grade: Da'if

Hadith #2208 - Sunan Abi Dawud - Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة; Zararah bin Awfa al-'Amiri al-Harshi زرارة بن أوفى العامري الحرشي (Sunan Abi Dawud)
What did you intend? He said: A single utterance of divorce. He said: Do you swear by Allah? He replied: I swear by Allah. He said: It stands as you intended. Abu Dawud said: This tradition is sounder than that of Ibn Juraij that Rukanah divorced his wife by three pronouncements, for they are the members of his family and they are more aware for him. The tradition of Ibn Juraij has been narrated by some children of Abu Rafi’ from ‘Ikrimah on the authority of Ibn ‘Abbas.
Grade: Da'if

Hadith #2211 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس (Sunan Abi Dawud)
Abu Tamimah reported from a man of his tribe “The Prophet (ﷺ) heard a man say his wife “O my younger sister! So he prohibited him (addressing his wife in this manner) Abu Dawud said “This tradition has also been transmitted by ‘Abd Al Aziz bin Al Mukhtar from Khalid from Abu ‘Uthman from Abu Thamimah from the Prophet (ﷺ). This has also been narrated by Shu’bah from Khalid from a man on the authority of Abu Thamimah from the Prophet (ﷺ).
Grade: Da'if

Hadith #2302 - Sunan Abi Dawud - Hafsa bint Umar; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Umm Atiyyah Ansariyah; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
‘Umm Athiyah reported the Prophet(ﷺ) as saying “A woman must not observe mourning for more than three (days) except for four months and ten days in the case of a husband and she must not wear a dyed garment except one of the types made of dyed yarn or apply collyrium or touch perfume except for a little costus or azfar when she has been purified after her menstrual courses. The narrator Ya’qub mentioned the words “except washed clothes” instead of the words “one of the types made o
Grade: Sahih

Hadith #2334 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
AbuIshaq reported on the authority of Silah: We were with Ammar on the day when the appearance of the moon was doubtful. (The meat of) goat was brought to him. Some people kept aloof from (eating) it. Ammar said: He who keeps fast on this day disobeys AbulQasim (i.e. the Prophet) (ﷺ).
Grade: Sahih

Hadith #2350 - Sunan Abi Dawud - Abdullah bin Da'ud al-Kharaybi عبد الله بن داود أبو عبد الرحمن الخريبي; Ahmad bin Hanbal أحمد بن حنبل; Hisham bin 'Urwa هشام بن عروة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Urwa ibn al-Zubayr عروة بن الزبير; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: When any of you hears the summons to prayer while he has a vessel in his hand, he should not lay it down till he fulfils his need.
Grade: Hasan Sahih

Hadith #2481 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
‘Amir said “A man came to ‘Abd Allaah bin ‘Amr while the people were with him. He sat with him and said “Tell me anything that you heard from the Apostle of Allaah(ﷺ)”. He said “I hears the Apostle of Allaah(ﷺ) say “A Muslim is he from whose tongue and hand the Muslims remain safe and an emigrant is he who abandons what Allaah has prohibited.””
Grade: Sahih

Hadith #2569 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Uthman bin Muhammad; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
Abu Hurairah reported the Apostle of Allaah(ﷺ) as saying “When you travel in fertile country, give the Camel their due (from the ground), and when you travel in time of drought make them go quickly. When you intend to encamp in the last hours of the night, keep away from the roads.”
Grade: Sahih

Hadith #2583 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi al-Hasan سعيد بن أبي الحسن (Sunan Abi Dawud)
The pommel of the sword of the Messenger of Allah (ﷺ) was of silver.
Grade: Sahih

Hadith #2655 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; al-Hasan al-Basri الحسن البصري; Hisham bin 'Urwa هشام بن عروة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة; Qays bin 'Aabad al-Qaysi قيس بن عباد القيسي الضبعي; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
I was present at fighting along with the Messenger of Allah (ﷺ), and when he did not fight at the beginning of the day, he waited till the sun had passed the meridian, the winds blew, and help came down.
Grade: Sahih

Hadith #2666 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: The most merciful of the people in respect of killing are believers (in Allah).
Grade: Da'if

Hadith #2793 - Sunan Abi Dawud - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) sacrificed seven camels standing with his own hand, and sacrificed at Medina two horned rams which were white with black markings.
Grade: Sahih

Hadith #2804 - Sunan Abi Dawud - Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) enjoined upon us to pay great attention to the eye and both ears, and not to sacrifice a one-eyed animal, and an animal with a slit which leaves something hanging at the front or back of the ear, or with a lengthwise slit with a perforation in the ear. I asked AbuIshaq: Did he mention an animal with broken horns and uprooted ears? He said: No. I said: ‘What is the Muqabalah ?’ He replied: ‘It has been cut from the back of its ear.’ I said: ‘What about the S
Grade: Da'if

Hadith #2839 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Khlf al-Bahly يحيى بن خلف الباهلي أبو سلمة البصري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Along with a boy there is an ‘Aqiqah, so shed blood on his behalf, and remove injury from him.
Grade: Sahih

Hadith #2886 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Kathir bin Hisham al-Klaby كثير بن هشام الكلابي أبو سهل الرقي; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Uthman bin Muhammad (Sunan Abi Dawud)
I fell ill, and the Prophet (ﷺ) and Abu Bakr came to me on foot to visit me. As I was unconscious, I could not speak to him. He performed ablution and sprinkled water on me ; so I became conscious. I said: Messenger of Allah, how should I do in my property, as I have sisters? Thereafter the verse about inheritance was revealed: “They ask thee for legal decision. Say: Allah directs (thus) about those who leave no descendants or ascendants as heirs.”
Grade: Sahih

Hadith #3085 - Sunan Abi Dawud - Aabad bin al-Wam bin عباد بن العوام; al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Ayoub al-Maqabri يحيى بن أيوب المقابري (Sunan Abi Dawud)
The Prophet (ﷺ) said: A fifth is payable on buried treasure.
Grade: Sahih

Hadith #3143 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Hafsa bint Sirin حفصة بنت سيرين; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
We braided her hair in three plaits.
Grade: Sahih

Hadith #3220 - Sunan Abi Dawud - Abdullah bin Bhyr عبد الله بن بحير; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Uthman ibn 'Affaan (Sunan Abi Dawud)
I said to Aisha! Mother, show me the grave of the Messenger of Allah (ﷺ) and his two Companions (Allah be pleased with them). She showed me three graves which were neither high nor low, but were spread with soft red pebbles in an open space. Abu ‘Ali said: It is said that the Messenger of Allah (ﷺ) is forward, Abu Bakr is near his head and ‘Umar is near is feet. His head is at the feet of the Messenger of Allah (ﷺ).
Grade: Hasan

Hadith #3296 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ikrama عكرمة; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
That the sister of ‘Uqbah b. ‘Amir took vow to walk on foot to the Ka’bah. Thereupon the Prophet (ﷺ) ordered her to ride and slaughter a sacrificial animal.
Grade: Sahih

Hadith #3708 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir bin Zayd al-Azdi جابر بن زيد الأزدي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Sunan Abi Dawud)
Safiyyah, daughter of Atiyyah, said: I entered upon Aisha with some women of AbdulQays, and asked her about mixing dried dates and raisins (for drink). She replied: I used to take a handful of dried dates and a handful or raisins and put them in a vessel, and then crush them (and soak in water). Then I would give it to the Prophet (ﷺ) to drink.
Grade: Da'if

Hadith #3716 - Sunan Abi Dawud - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
I knew that the Messenger of Allah (ﷺ) used to keep fast. I waited for the day when he did not fast to present him the drink (nabidh) which I made in a pumpkin. I then brought it to him while it fermented. He said: Throw it to this wall, for this is a drink of the one who does not believe in Allah and the Last Day.
Grade: Sahih

Hadith #3726 - Sunan Abi Dawud - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي (Sunan Abi Dawud)
The Prophet (ﷺ) was brought milk that was mixed with water. A nomad Arab was on his right and Abu Bakr was on his left. He himself drank and gave it to the nomad Arab, and said: He who is on the right , then he who is on his right then he who is on his right.
Grade: Sahih

Hadith #3745 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
The Prophet (ﷺ) said: The wedding feast on the first day is a duty, that on the second is a good practice, but that on the third day is to make men hear of it and show it to them. Qatadah said: A man told me that Sa’id ibn al-Musayyab was invited (to a wedding feast on the first day and he accepted it. He was again invited on the second day, and he accepted. When he was invited on the third day, he did not accept; he said: They are the people who make men hear of it and show it to them.
Grade: Da'if

Hadith #3766 - Sunan Abi Dawud - Aisha bint Abi Bakr; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي (Sunan Abi Dawud)
The devil considers the food when Allah’s name is not mentioned over it, and he brought his nomad Arab that it might be lawful by means of him, so I seized his hand: then he brought this girl that it might be lawful by means of her, so I seized her hand. By Him in Whose hand my soul is, His hand is in my hand along with their hands.
Grade: Sahih

Hadith #3785 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Ikrama عكرمة; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited eating the animal which feeds on filth and drinking its milk.
Grade: Sahih

Hadith #3862 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي (Sunan Abi Dawud)
(the narrator other than Musa said that Kayyisah daughter of AbuBakrah) She said that her father used to forbid his family to have themselves cupped on a Tuesday, and used to assert on the authority of the Messenger of Allah (ﷺ) that Tuesday is the day of blood in which there is an hour when it does not stop.
Grade: Da'if

Hadith #3915 - Sunan Abi Dawud - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
I asked Muhammad b. Rashid about the meaning of the word hamah. He replied: The pre-Islamic Arabs used to say: When anyone dies and is buried, a bird comes forth from his grave. I asked: What did he mean by safar ? He said: I heard that the pre-Islamic Arabs used to take evil omen from safar. So the Prophet (ﷺ) said: There is no safar. Muhammad (b. Rashid) said: We heard someone say: It is a pain in the stomach. They said that it was infection. Hence he said: There is no safar.
Grade: Sahih

Hadith #3919 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Burayda bin al-Husayb; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
When taking omens was mentioned in the presence of the Prophet (ﷺ), he said: The best type is the good omen, and it does not turn back a Muslim. If one of you sees anything he dislikes, he should say: O Allah, no one brings good things except Thee, and no one averts evil things except Thee and there is no might and power but in Allah.
Grade: Da'if

Hadith #3935 - Sunan Abi Dawud - Ahmed bin 'Ali al-Nmyry أحمد بن علي النميري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء (Sunan Abi Dawud)
The Prophet (ﷺ) said: If a man emancipates a slave shared by him with another man, his emancipation rests with him (who emancipated his share). This is the version of Ibn Suwaid.
Grade: Sahih

Hadith #3964 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ma'dan bin Abi Talha معدان بن أبي طلحة ويقال بن طلحة; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Salm bin Abi al-Ja'd سالم بن أبي الجعد (Sunan Abi Dawud)
Al-Arif ibn ad-Daylami said: We went to Wathilah ibn al-Asqa and said to him: Tell us a tradition which has not addition or omission. He became angry and replied: One of you recites when his copy of a Qur’an is hung up in his house, and he makes additions and omissions. We said: All we mean is a tradition you have heard from the Messenger of Allah (ﷺ). He said: We went to the Prophet (ﷺ) about a friend of ours who deserved. Hell for murder. He said: Emancipate a slave on his behalf; Allah
Grade: Hasan

Hadith #4026 - Sunan Abi Dawud - Asma' bint Yazid bin al-Sakan; Badayl bin Maysarah بديل بن ميسرة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Rahwaya إسحاق بن راهويه; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري (Sunan Abi Dawud)
No clothing was dearer to be Messenger of Allah (ﷺ) than shirt.
Grade: Sahih

Hadith #4049 - Sunan Abi Dawud - Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Ubaida bin 'Amr al-Salamani عبيدة بن عمرو; Yahya bin Habib bin Arby يحيى بن حبيب بن عربي (Sunan Abi Dawud)
my companion went to the mosque before me. I went there after him and sat beside him. He asked me: Did you hear the preaching of AbuRayhanah? I said: No. He said: I heard him say: The Messenger of Allah (ﷺ) forbade ten things: Sharpening the ends of the teeth, tattooing, plucking hair, men sleeping together without an under garment, women sleeping together without an under-garment, men putting silk at the hem of their garments like the Persians, or putting silk on their shoulders like the Pers
Grade: Da'if

Hadith #4091 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: He who has in his heart as much pride as much pride as grain of mustard-seed will not enter paradise. And he who has in his heart as much faith as grain of mustard-seed will not enter Hell. Abu Dawud said: Al-Qasmali has transmitted it from Al-A’mash in a similar way.
Grade: Sahih

Hadith #4146 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي (Sunan Abi Dawud)
The pillow of the Messenger of Allah (ﷺ) on which he slept at night (according to the version on Ibn Mani’) was of leather stuffed with palm fibre (according to the agreed version).
Grade: Sahih

Hadith #4285 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل (Sunan Abi Dawud)
The Prophet (ﷺ) said: The Mahdi will be of my stock, and will have a broad forehead a prominent nose. He will fill the earth will equity and justice as it was filled with oppression and tyranny, and he will rule for seven years.
Grade: Hasan

Hadith #4366 - Sunan Abi Dawud - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent some people who were experts in tracking in pursuit of them and they were brought (to him). Allah , the Exalted, then revealed the verse about it : “ The punishment of those who wage war against Allah and his Apostle and strive for mischief through the land.
Grade: Sahih

Hadith #4477 - Sunan Abi Dawud - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
When a man who had drunk wine was brought to the Messenger of Allah (ﷺ), he said: Beat him. Abu Hurairah said: Some struck him with their hands, some with their garment. When he turned his face, some people said: Allah put you shame! The Messenger of Allah (ﷺ) said: Do not say like that and help the devil to get power over him.
Grade: Sahih

Hadith #4514 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Abi Dawud)
On the authority of his mother than Umm Mubashshir said (Abu Sa’id b. al-A’rabi said: So he said it on the authority of his mother ; what is correct is: on the authority of his father, instead of his mother): I entered upon the Prophet (ﷺ). He then mentioned the tradition of Makhlad b. Khalid in a way similar to the tradition of Jabir. The narrator said: Then Bishr b. al-Bara’ b. Ma’rur died. So he (the Prophet) sent for the Jewess and said: What did motivate you for your work you have
Grade: Sahih

Hadith #4516 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
Through the same chain of narrators as mentioned before, i.e. Samurah reported the Messenger of Allah (ﷺ) as saying: If anyone castrates his slave, we shall castrate him. He then mentioned the rest of the tradition like that of Sh’ubah and Hammad. Abu Dawud said: Abu Dawud al-Tayalisi transmitted it from Hisham like the tradition of Mu’adh.
Grade: Hasan

Hadith #4568 - Sunan Abi Dawud - al-Miswar bin Makhrama bin Nawfal; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Urwa ibn al-Zubayr عروة بن الزبير; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
A man of Hudhail has two wives. One of them struck her fellow-wife with a tent-pole and killed her and her unborn child. They brought the dispute to the Prophet (ﷺ). One of two men said: How can we pay bloodwit for the one who did not make a noise, or ate, nor drank, nor raised his voice ? He (the Prophet) asked: Is it rhymed prose like that of bedouin? He gave judgement that a male or female slave of the best quality should be paid in compensation, and he fixed it to be paid by woman’s rela
Grade: Sahih

Hadith #4588 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Imran bin Husain; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Musaddad’s version has: He addressed on the day of Conquest. The agreed version then goes: Beware! Every object of pride of pre-Islamic times, whether it is blood-vengeance or property, mentioned or claimed, has been put under my feet except supply of water to the pilgrims and custody of the House (the Ka’bah). He then said: Beware! The blood-wit for unintentional murder, such as is done with a whip and stick, is one hundred camels, forty of which are pregnant.
Grade: Sahih

Hadith #4661 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
When the Prophet (May peace be upon him) heard ‘Umar’s voice, Ibn Zam’ah said: The Prophet (May peace be upon him) came out until he took out his head of his apartment. He then said : No, no, no; the son of Abu Quhafah should lead the people in prayer. He said it angrily.
Grade: Sahih

Hadith #4759 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Umm Salamah (Sunan Abi Dawud)
How will you deal with the rulers (imams) who appropriate to themselves this booty? I said : I swear by him who sent you with the truth that at that time I shall put my sword on my shoulder and smite with it till I meet you, or I join you. He said: shall I not guide you to something better than that? You must show endurance till you meet me.
Grade: Hasan

Hadith #4904 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة; Samra bin Jundub (Sunan Abi Dawud)
Sahl ibn AbuUmamah said that he and his father (AbuUmamah) visited Anas ibn Malik at Medina during the time (rule) of Umar ibn AbdulAziz when he (Anas ibn Malik) was the governor of Medina. He was praying a very short prayer as if it were the prayer of a traveller or near it. When he gave a greeting, my father said: May Allah have mercy on you! Tell me about this prayer: Is it obligatory or supererogatory? He said: It is obligatory; it is the prayer performed by the Messenger of Allah (ﷺ). I d
Grade: Da'if

Hadith #4928 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Ikrama عكرمة; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
Am effeminate man (mukhannath) who had dyed his hands and feet with henna was brought to the Prophet (ﷺ). He asked: What is the matter with this man? He was told: “Messenger of Allah! He imitates the look of women.” So he issued an order regarding him and he was banished to an-Naqi’. The people said: Messenger of Allah! Should we not kill him? He said: I have been prohibited from killing people who pray. AbuUsamah said: Naqi’ is a region near Medina and not a Baqi’.
Grade: Sahih

Hadith #4964 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي (Sunan Abi Dawud)
The Prophet (ﷺ) said to him: My sonny. Abu Dawud said: I heard Yahya b. Ma’in praising the transmitter Muhammad b. Mahbub, and he said: He transmitted a large number of traditions.
Grade: Sahih

Hadith #4975 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Burayda bin al-Husayb; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري (Sunan Abi Dawud)
The Prophet (ﷺ) said: None of you must say: “My slave” (abdi) and “My slave-woman” (amati), and a slave must not say: “My lord” (rabbi or rabbati). The master (of a slave) should say: “My young man” (fataya) and “My young woman” (fatati), and a slave should say “My master” (sayyidi) and “My mistress” (sayyidati), for you are all (Allah’s slave and the Lord is Allah, Most High.
Grade: Sahih

Hadith #5038 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
The Jews used to try to sneezes in the presence of the Prophet (ﷺ) hoping that he would say to them: “Allah have mercy on you!” but he would say: May Allah guide you and grant you well-being!
Grade: Sahih

Hadith #5181 - Sunan Abi Dawud - Abdul Qahir bin Shu'iab bin al-Habhab عبد القاهر بن شعيب بن الحبحاب; Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; Hameed bin Hilal حميد بن هلال; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Zayd bin Akhzm زيد بن أخزم (Sunan Abi Dawud)
Abu Musa asks permission, al-Ash’ari ask permission, and ‘Abd Allah b. Qais asks permission, but it was not granted to him. So he went away and ‘umar sent for him saying: what did you return? He replied: The Messenger of Allah (May peace be upon him) said: When one of you asks permission three times and it is not granted to him, he should go away. He said: Establish the proof of it. He went, came back, and said; This is Ubayy. Ubayy said: ‘Umar, do not be an agony for the Companions of t
Grade: Hasan

Hadith #5224 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Zayd bin Wahb al-Jhny زيد بن وهب الجهني (Sunan Abi Dawud)
AbdurRahman ibn AbuLayla, quoting Usayd ibn Hudayr, a man of the Ansar, said that while he was given to jesting and was talking to the people and making them laugh, the Prophet (ﷺ) poked him under the ribs with a stick. He said: Let me take retaliation. He said: Take retaliation. He said: You are wearing a shirt but I am not. The Prophet (ﷺ) then raised his shirt and the man embraced him and began to kiss his side. Then he said: This is what I wanted, Messenger of Allah!
Grade: Sahih

Hadith #180 - Jami' al-Tirmidhi - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Umar ibn al-Khattab; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Jami' al-Tirmidhi)
“On the Day of Al-Khandaq (the battle of the Trench), Umar bin Al-Khattab came cursing the disbelievers of Quraish and said: ‘O Allah’s Messenger! I could not offer he Asr prayer until the sun was about to set.’ The Prophet said: ‘By Allah! I too have not offered the Salat.'” So he said: “We descended into Buthan, Allah’s Messenger performed Wudu and we too performed Wudu. Allah’s Messenger prayed Asr after the sun had set, then after it he prayed Maghrib.”
Grade:

Hadith #396 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Jami' al-Tirmidhi)
the Prophet (S) led them in Salat he forgot (something) so he performed two prostrations, then the Tashah-hud, then the Salam.
Grade:

Hadith #610 - Jami' al-Tirmidhi - Abu Harb bin Abi al-Aswad أبو حرب بن أبي الأسود الديلي; Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Jami' al-Tirmidhi)
the Messenger of Allah said, about urine of a male child that suckles: “The urine of the boy is sprinkled, and the girl’s urine is washed.” Qatadah (one of the narrators) said: “This is so, as long as they do not eat, when they eat, then both of them are washed.”
Grade:

Hadith #703 - Jami' al-Tirmidhi - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Qatada قتادة; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي; Yahya bin Musa Khat يحيى بن موسى خت; Zayd ibn Thabit (Jami' al-Tirmidhi)
Zaid bin Thabit said: “We ate Sahar with the Messenger of Allah, then we stood for the Salat.” I (Anas) said: “How long was that?” He said: “About the lengthy of fifty Ayahs.”
Grade:

Hadith #906 - Jami' al-Tirmidhi - Abu Hsan al-A'rj أبو حسان الأعرج; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Qatada قتادة; Waki' bin al-Jarrah وكيع بن الجراح (Jami' al-Tirmidhi)
“We were with the Prophet on a journey (on the Day of) Adha, so seven of us shared in a cow, and ten for a camel.”
Grade:

Hadith #1041 - Jami' al-Tirmidhi - Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hassan ibn Ali bin Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Nasr bin 'Ali bin Nasr bin 'Ali; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Jami' al-Tirmidhi)
“I accompanied Abu Hurairah for ten years, and I heard him saying: ‘I heard the Messenger of Allah saying: “Whoever follows a funeral, and carries it three times, then he has fulfilled the right that is required from him.”
Grade:

Hadith #1080 - Jami' al-Tirmidhi - al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Yazid Abu Hisham al-Rafa'i محمد بن يزيد أبو هشام الرفاعي; Qatada قتادة; Samra bin Jundub; Zayd bin Akhzm زيد بن أخزم (Jami' al-Tirmidhi)
The Messenger of Allah said: “Four are from the Sunan of the Messengers: Al-Hayat, using Atar, the Siwak, and marriage.”
Grade:

Hadith #1498 - Jami' al-Tirmidhi - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmed bin Manay' أحمد بن منيع; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Yusuf bin Mrdas إسحاق بن يوسف بن مرداس; Thabit bin al-Dahhak bin Khalifa; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Jami' al-Tirmidhi)
Another chain from the Prophet (ﷺ) with similar meaning.
Grade:

Hadith #1514 - Jami' al-Tirmidhi - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmed bin Manay' أحمد بن منيع; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Yusuf bin Mrdas إسحاق بن يوسف بن مرداس; Thabit bin al-Dahhak bin Khalifa; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Jami' al-Tirmidhi)
“I said to the Mother of the Believers: ‘Did the Messenger of Allah (ﷺ) prohibit from the meat of the sacrifice?’ She said: ‘No, but only a few people could slaughter, so he liked that they feed those who did not slaughter. (Later) we would store a leg to eat after ten days.”
Grade:

Hadith #1576 - Jami' al-Tirmidhi - al-Nu'man bin Maqrn al-Mazni; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Jami' al-Tirmidhi)
That the Prophet (ﷺ) ransomed two men for the Muslims with a man from the idolaters. This Hadith is Hasan Sahih. The paternal uncle of Abu Al-Muhallab’s name is ‘Abdur Rahman bin ‘Amr, and they also say it was Muhawiyah bin ‘Amr. And Abu Qilabah’s name is ‘Abdullah bin Zaid Al-Jarmi (narrator in the chain) This is acted upon according to most of the people of knowledge among the Companions of the Prophet(ﷺ) and others. It is for the Imam to decide to be generous with whom he wil
Grade:

Hadith #1579 - Jami' al-Tirmidhi - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Jami' al-Tirmidhi)
“The Messenger of Allah (ﷺ) sent us with an army and said: ‘If you see so-and-so, and so-and-so’ referring to two men from the Quraish: ‘then burn them with fire.’ Then, upon our departure, the Messenger of Allah (ﷺ) said: ‘I ordered you to burn so-and-so, and so-and-so with fire, and indeed, none punishes with fire except Allah. So if you see them, then kill them.'” There are narrations on this topic from Ibn ‘Abbas and Hamzah bin ‘Amr Al-Aslami. The Hadith of Abu Huraira
Grade:

Hadith #1602 - Jami' al-Tirmidhi - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ma'dan bin Abi Talha معدان بن أبي طلحة ويقال بن طلحة; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Salm bin Abi al-Ja'd سالم بن أبي الجعد (Jami' al-Tirmidhi)
“We used to pledge to the Messenger of Allah (ﷺ) to hear and obey.” So he would say to us: “As much as you are able.” This Hadith is Hasan Sahih.
Grade:

Hadith #1625 - Jami' al-Tirmidhi - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Jami' al-Tirmidhi)
That the Messenger of Allah (ﷺ) said: “There is no ‘Adwa and no Tiyarah, and I like Fa’l.” They said: “O Messenger of Allah! What is Fa’l?” He said: “A good statement.” This Hadith is Hasan Sahih.
Grade:

Hadith #1672 - Jami' al-Tirmidhi - Amir al-Sha'bi عامر الشعبي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Suwayd bin Ghaflah bin Awsajah سويد بن غفلة بن عوسجة; Umar ibn al-Khattab (Jami' al-Tirmidhi)
That Ibn Juraij commented on Allah’s saying: Obey Allah and obey the Messenger, and those in authority among you. He said: “Abdullah bin Hudhafah bin Qais bin ‘Adi As-Sahmi was sent by the Messenger of Allah (ﷺ) over a military expedition. I was informed of that by Ya’la bin Muslim, from Sa’eed bin Jubair, from Ibn ‘Abbas. This Hadith is Hasan Sahih Gharib. We do not know if it except as a narration of Ibn Juraij.
Grade:

Hadith #1735 - Jami' al-Tirmidhi - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Jami' al-Tirmidhi)
“On the day of the Conquest, the Prophet (ﷺ) entered Makkah, and he was wearing a black ‘Imamah.” THere are narrations on this topic from ‘Ali, ‘Amr bin Huraith, Ibn ‘Abbas, Rukanah. The Hadith is Jabir is Hasan Sahih Hadith.
Grade:

Hadith #1736 - Jami' al-Tirmidhi - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Jami' al-Tirmidhi)
That Ibn ‘Umar said: “When the Messenger of Allah (ﷺ) would wear an ‘Imamah would hang between his shoulders.” Nafi’ said: “Ibn ‘Umar would hang his ‘Imamah between his shoulders.” ‘Ubaidullah said: “And I saw Al-Qasim and Salim doing that.” This Hadith is Hasan Gharib. And there is something on this topic from ‘Ali. And this Hadith of ‘Ali about this is not correct due to its chain.
Grade:

Hadith #1773 - Jami' al-Tirmidhi - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Ikrama عكرمة; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Jami' al-Tirmidhi)
“My nose was severed on the Day of Al-Kulab during Jahiliyyah. So I got a nose of silver which caused an infection for me, so the Messenger of Allah (ﷺ) ordered me to get a node made of gold.”
Grade:

Hadith #1798 - Jami' al-Tirmidhi - Abdullah bin 'Ubaid bin 'Umayr عبد الله بن عبيد بن عمير; Aisha bint Abi Bakr; Badayl bin Maysarah بديل بن ميسرة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Aban bin Wzyr محمد بن أبان بن وزير البلخي; Umm Khultum bint Abi Bakr أم كلثوم بنت أبي بكر الصديق; Waki' bin al-Jarrah وكيع بن الجراح (Jami' al-Tirmidhi)
That he said: “O Messenger of Allah! We live in a land of the People of Book and we cook in their containers, and drink in their vessels.” The Messenger of Allah (ﷺ) said: “If you do not find other than them, then rinse them with water.” The he said: “O Messenger of Allah! We live in a land of game, so what should we do ?” He said: “When you send your trained dog, and you mentioned the Name of Allah, and he kills it, then eat it. And when you shoot it with your bow, and it is kil
Grade:

Hadith #1829 - Jami' al-Tirmidhi - Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Jami' al-Tirmidhi)
“I entered upon Abu Musa while he was eating chicken, and he said: ‘Sit and eat, for indeed I saw the Messenger of Allah (ﷺ) eating it.'” This Hadith is Hasan. This Hadith has been reported through other routes from Zahdam, and we do not know of it except as the narration of Zahdam. (One of the narrators) Abu Al-‘Awwam is ‘Imran Al-Qattan.
Grade:

Hadith #1963 - Jami' al-Tirmidhi - Abu Hurairah; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Jami' al-Tirmidhi)
“Generosity is close to Allah, close to Paradise, close to the people and far from the Fire. Stinginess is far from Allah, far from Paradise, far from the people and close to the Fire. The ignorant generous person, is more beloved to Allah than the worshiping stingy person.”
Grade:

Hadith #2036 - Jami' al-Tirmidhi - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Samra bin Jundub (Jami' al-Tirmidhi)
“When Allah loves a slave, He prevents him from the world, just as one of you prevents his sick from water.” Another chain reports a similar narration.
Grade:

Hadith #2141 - Jami' al-Tirmidhi - Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري (Jami' al-Tirmidhi)
“When Allah wants good for a slave, He puts him in action.” It was said: “How does he put him in action O Messenger Of Allah?” He said: “By making him meet up with the righteous deeds before death.”
Grade:

Hadith #2143 - Jami' al-Tirmidhi - Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Jami' al-Tirmidhi)
‘A slave (of Allah) shall not believe until he believes in Al-Qadar, its good and its bad, such that he knows that what struck him would not have missed him, and that what missed him would not have struck him.”
Grade:

Hadith #2153 - Jami' al-Tirmidhi - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Zayd bin Arqam (Jami' al-Tirmidhi)
” Six are cursed, being cursed by Allah and by every Prophet that came: The one who adds to Allah’s Book, the one who denies Allah’s Qadar, the one who rules with tyranny by which he honors whom Allah has debased, and he dishonors whom Allah has honored, and the one who legalizes what Allah forbade, and the one from my family who legalizes what Allah forbade, and the abandoner of my Sunnah.”
Grade:

Hadith #2664 - Jami' al-Tirmidhi - Abu Hurairah; Amir bin Abd al-Wahd عامر بن عبد الواحد الأحول البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Yazid Abu Hisham al-Rafa'i محمد بن يزيد أبو هشام الرفاعي; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري (Jami' al-Tirmidhi)
“We sought permission from the Messenger of Allah (ﷺ) for writing but he did not permit us.”
Grade:

Hadith #2691 - Jami' al-Tirmidhi - Abu Sa'id al-Khudri; Amir bin Abd al-Wahd عامر بن عبد الواحد الأحول البصري; Bakr bin 'Amr Abu al-Siddique al-Naji بكر بن عمرو/ قيس; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار (Jami' al-Tirmidhi)
“A man enter the Masjid and performed Salat while the Messenger of Allah (ﷺ) was sitting at the back of the Masjid. Then he came to greet him, so the Prophet (ﷺ) said: “Wa Alaikum (and upon you); go back and pray for indeed you have not prayed.'” And he mentioned the Hadith in its entirety.
Grade:

Hadith #3044 - Jami' al-Tirmidhi - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Jami' al-Tirmidhi)
“Ibn Abbas recited: This day, I have perfected your religion for you, completed My favor upon you, and have chosen for you Islam as your religion (5:3). And a Jew was with him who said: ‘If this Ayah was revealed to us then we would have taken that day as a day of celebration.’ So Ibn ‘Abbas said: ‘Indeed it was revealed on two ‘Eids: On Friday, and on the Day of ‘Arafah.'”
Grade:

Hadith #3457 - Jami' al-Tirmidhi - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Khalid bin al-Lajlaj al-Amiri خالد بن اللجلاج العامري; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Jami' al-Tirmidhi)
The Messenger of Allah (ﷺ) said: “Whoever eats food and then says: ‘All praise is due to Allah who fed me this and granted it as provision to me, without any effort from me nor power, (Al-ḥamdulillāh, alladhī aṭ`amanī hādha wa razaqanīhi min ghairi ḥawlin minnī, wa lā quwwatin)’ his past sins shall be forgiven.”
Grade:

Hadith #3888 - Jami' al-Tirmidhi - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Ikrama عكرمة; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin Bashar Bindar محمد بن بشار بندار (Jami' al-Tirmidhi)
that the Messenger of Allah (ﷺ) appointed him as a leader of the army of Dhatis-Salasil. He said: “So I went to him and said: ‘O Messenger of Allah! Who is the most beloved to you among the people?’ He said: ”Aishah.’ I said: ‘From the men?’ He said: ‘Her father.'”
Grade:

Hadith #411 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Umm Salamah; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Zaynab bint Abi Salamah (Sunan Ibn Majah)
“The Messenger of Allah said: ‘When it is very hot, then wait for it to cool down before you pray, for intense heat is from the flaring up of the Hell-fire.'”
Grade:

Hadith #567 - Sunan Ibn Majah - Abu Harb bin Abi al-Aswad أبو حرب بن أبي الأسود الديلي; Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan Ibn Majah)
“The Prophet (ﷺ) used to recite in the Maghrib: ‘Say: O you disbelievers!’ and ‘Say: He is Allah, (the) One.’”
Grade:

Hadith #653 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Abu Rafi'; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Qatada قتادة (Sunan Ibn Majah)
It was narrated from Hisham bin ‘Urwah, from his father, from ‘Aishah, that the Messenger of Allah (saW) used to say one Salam, to the front.
Grade:

Hadith #794 - Sunan Ibn Majah - al-Hakam bin Myna'a al-Ansari Mwlahm الحكم بن ميناء; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“And also upon you. Go back and repeat your prayer, for you have not prayed.” So he went back and repeated his prayer, then he came and greeted the Prophet (ﷺ). He said: “And also upon you. Go back and repeat your prayer, for you have not prayed.” On the third occasion, the man said: “Teach me, O Messenger of Allah!” He said: “When you stand up to offer the prayer, perform ablution properly, then stand to face the prayer direction and say Allahu Akbar. Then recite whatever you ca
Grade:

Hadith #878 - Sunan Ibn Majah - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Bashr bin Hilal al-Swaf بشر بن هلال الصواف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Yazid bin Zari' يزيد بن زريع (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) used to pray two Rak’ah before the morning (prayer), as if the Adhan were in his ears. (i.e., he would pray them briefly).
Grade:

Hadith #908 - Sunan Ibn Majah - Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Malik bin al-Hwyrth; Nsr bin 'Asim al-Lythy نصر بن عاصم الليثي البصري; Qatada قتادة; Yazid bin Zari' يزيد بن زريع (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) used to pray (voluntary prayers) at night two by two, and he would pray one Rak’ah of Witr.”
Grade:

Hadith #1003 - Sunan Ibn Majah - Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Sa'd bin Hisham bin 'Amir سعد بن هشام بن عامر; Zararah bin Awfa al-'Amiri al-Harshi زرارة بن أوفى العامري الحرشي; Zayd bin Akhzm زيد بن أخزم (Sunan Ibn Majah)
“O Ka’b bin Murrah, narrate to us a Hadith from the Messenger of Allah (ﷺ), but be careful.” He said: “A man came to the Prophet (ﷺ) and said: ‘O Messenger of Allah, ask Allah for rain!’ So the Messenger of Allah (ﷺ) raised his hands and said: ‘O Allah! Send wholesome, productive rain upon all of us, sooner rather than later, beneficial and not harmful.’ No sooner had they finished performing Friday (prayer) but they were revived. Then they came to him and complained to him
Grade:

Hadith #1049 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin Ma'dan خالد بن معدان; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) used to have a bath on the day of Fitr and the day of Adha.”
Grade:

Hadith #1261 - Sunan Ibn Majah - Amr bin Rafa'i al-Advi. Client Of 'Umar عمرو بن رافع العدوي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“Why did you not tell me?” Then he went to her grave and offered the funeral prayer for her.
Grade:

Hadith #1301 - Sunan Ibn Majah - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة; Yazid bin Zari' يزيد بن زريع (Sunan Ibn Majah)
‘If I were to walk on a live coal or a sword, or if I were to sew shows to my feet, that would be better for me than walking on the grave of a Muslim. And I see no difference between relieving myself in the midst of graves or in the middle of the marketplace.”
Grade:

Hadith #1764 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Qatada قتادة; Waki' bin al-Jarrah وكيع بن الجراح; Zayd ibn Thabit (Sunan Ibn Majah)
“By Allah, for those who would like to go through the process of praying for Allah’s curse to be upon the one who is wrong, the shorter Surah concerning women (2:234)
Grade:

Hadith #1838 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
‘Whoever swears an oath and says In sha’ Allah, he will have made an exception.”(2)
Grade:

Hadith #1922 - Sunan Ibn Majah - al-Hasan al-Basri الحسن البصري; Bashr bin Adam al-Dareer بشر بن آدم الضرير; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Zayd bin Akhzm زيد بن أخزم (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘It is not permissible to sell something that is not with you, nor to profit from what you do not possess.”‘
Grade:

Hadith #2100 - Sunan Ibn Majah - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Umar; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Nasr bin 'Ali bin Nasr bin 'Ali; Yonus bin Jubayr al-Bahli, Abu Ghalab يونس بن جبير الباهلي أبو غلاب (Sunan Ibn Majah)
“The Testimony of a man or woman who is treacherous, or of one who has been subjected to one of the Haad punishments of Islam, or of one who bears a grudge against his brother, is not permissible.”
Grade:

Hadith #2151 - Sunan Ibn Majah - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sa'id bin Jubayr سعيد بن جبير الأسدي; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Y'la bin Hkym al-Thqfy يعلى بن حكيم الثقفي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
Whoever is easy with (a debtor) who is in difficulty, Allah will be easy with him in this world and in the Hereafter.”
Grade:

Hadith #2173 - Sunan Ibn Majah - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Abdur Rahman bin Samra; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Hasan al-Basri الحسن البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي (Sunan Ibn Majah)
the Messenger of Allah (ﷺ) died while his armor was pawned to a Jew for thirty Sa’s of barley.’ ”
Grade:

Hadith #2529 - Sunan Ibn Majah - Ali bin Nasr bin 'Ali al-Jahdami Older علي بن نصر بن علي الجهضمي الكبير; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة (Sunan Ibn Majah)
“There is no one who is wounded in the cause of Allah – and Allah knows best of who is wounded in His cause – but he will come on the Day of Resurrection with his wounds looking as they did on the day he was wounded; their color will be the color of blood but their smell will be the fragrance of musk.”
Grade:

Hadith #2665 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة; Sa'id bin Abi Sa'id; Waki' bin al-Jarrah وكيع بن الجراح; Yazid bin Zari' يزيد بن زريع (Sunan Ibn Majah)
“I heard the Prophet (ﷺ) delivering a sermon – (one of the narrators) Hisham said: ‘On the pulpit’ – and he said: ‘Whoever does not have a waist wrap, let him wear pants or pajamas, and whoever does not have sandals, let him wear leather socks.’” In his narration, Hisham said: “If he does not find any, then let him wear pants or pajamas.”
Grade:

Hadith #2916 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Uqba bin 'Amir al-Juhayni; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
It was narrated from a son of Ka’b bin Malik, from his father, that a woman slaughtered a sheep with a stone, and that was mentioned to the Messenger of Allah (ﷺ), but he did not see anything wrong with that.
Grade:

Hadith #3099 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Badayl bin Maysarah بديل بن ميسرة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Safiyya bint Shayba bin 'Uthman; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Did I not forbid you to eat these vegetables? For the angels are offended by that which offends people.”
Grade:

Hadith #3214 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hsan al-A'rj أبو حسان الأعرج; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Abbas; Qatada قتادة; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
It was narrated from Jabir that Umm Salamah, the wife of the Prophet (ﷺ), asked the Messenger of Allah (ﷺ) for permission to be cupped, and the Prophet (ﷺ) told Abu Taibah to cup her.
Grade:

Hadith #3229 - Sunan Ibn Majah - Ayoub al-Sakhtiyani أيوب السختياني; Bakr bin Khlf al-Basri بكر بن خلف البصري; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; ibn Umar; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Nafie' نافع مولى ابن عمر (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘You should use antimony, for it improves the eyesight and makes the hair (eyelashes) grow.’”
Grade:

Hadith #3386 - Sunan Ibn Majah - Abdullah bin 'Ubaid bin 'Umayr عبد الله بن عبيد بن عمير; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Badayl bin Maysarah بديل بن ميسرة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
It was narrated from Abu Umamah that a woman came to the Prophet (ﷺ) and told him that her husband was away on some military campaign. She asked him for permission to make an image of a palm tree in her house, and he did not let her, or he forbade her.
Grade:

Hadith #3415 - Sunan Ibn Majah - Anas ibn Malik; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan Ibn Majah)
“O Messenger of Allah! Tell me of an action by which I may benefit.’ He said: ‘Remove harmful things from the path of the Muslims.'”
Grade:

Hadith #3482 - Sunan Ibn Majah - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The Messenger of Allah(ﷺ) said: ‘You will conquer the lands of the non-Arabs, where you will find houses called Hammamat (bathhouses). Men Should only enter them wearing a waist wrap, and do not let women enter them unless they are sick or bleeding following childbirth.”
Grade:

Hadith #3860 - Sunan Ibn Majah - Abdullah bin Bakr عبد الله بن بكر بن حبيب السهمي; Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“The poor Muhajirun complained to the Messenger of Allah (ﷺ) about that with which Allah had favored the rich over them. He said: ‘O poor people, shall I not give you the glad tidings that the poor believers will enter Paradise half a day, five hundred years, before the rich?’”
Grade: